Commoning in the practice of urban governance. An experience from OBRAS project - Andrea Boeri; Danila Longo; Martina Massari; Rossella Roversi; Francesca Sabatini (Agathón)
The complexity of the contemporary urban scenario, now in constant revolution, calls for new forms of governance: able to combine the stances of institutional actors, civil society and the entrepreneurial world; commoning, born as a form of bottom-up re-appropriation of neglected spaces, has now become a multi-scalar, shared practice, which inspired the approach of the OBRAS project analysed here. In the first section the literary review frames the research context, with reference to urban commoning practices for the re-activation of places, and its relation with urban governance; in the second section, the methodology and physical context of the workshops, Bologna and Bogotá, are introduced. The methodology and results of the project are presented in the third section: the multi-scalar, cross-cutting and shared practices adopted and the meta-project solutions produced. The fourth section summarizes the OBRAS experience, with results, limits and future developments of the project.